Electron-hole pair creation and conversion efficiency in radioisotope microbatteries. (February 2022) - Lioliou, G.; Barnett, A.M.
Abstract: The ultimate conversion efficiency of semiconductor radioisotope microbatteries is set by the average energy consumed in the creation of an electron-hole pair, ω . Although the Klein relationship between ω and semiconductor bandgap, E g, is widely cited, not only for radioisotope microbatteries, but indeed for a multitude of fields requiring accurate values of ω, its validity has been recently questioned; new experimental measurements have resulted in the refined Bertuccio-Maiocchi-Barnett (BMB) relationship. Here, it is shown that the new relationship indicates the ultimately achievable conversion efficiencies of radioisotope microbatteries are much greater than had ever been expected. For example, it appears possible to produce planar 63 Ni-Diamond radioisotope microbatteries with output powers 130× greater than has currently been achieved. The ultimate limit for batteries employing pore channels rather than planar designs is likely to be even greater still. These new findings open the possibility of using radioisotope microbatteries in a far greater variety of applications than has been traditionally assumed. As well as being of direct applicability to radioisotope microbatteries, the results highlight the need to reconsider the use of the Klein relationship in all fields that currently employ it. Highlights: The conversion efficiency of radioisotope microbatteries has been reconsidered. Ultimate conversion efficiencies are much higher than traditionally expected. All materials with bandgaps >1.1 eV are affected. 63 Ni-diamond batteries may have 130 × higher output power than so far achieved.